Persepsi Mahasiswa Akuntansi dan Akuntan Pendidik Binus University Mengenai Aturan Etika dalam Kode Etik Ikatan Akuntan Indonesia 2010 - Hermanto, Ficha; Sudarmo, Sudarmo; Ramdan, Zulfitry (Bina Nusantara University, 2012)
The purpose of this research is to find out the perception difference between Binus University accounting lecturers and students in understanding Ikatan Akuntan Indonesia (IAI) code of conduct.The code of conduct consists of five elements, those are independence, integrity and objectivity; common standards and accounting principles; responsibility to clients; responsibility to colleagues; responsibility and other practice. This research gathered the primary data through questionnaires about code of conduct from accounting lecturers and students in Binus University. The hypothesis has been analyzed with Independent t-test. The result shows that there is only one perception difference, which is in responsibility to clients. It is caused by experience difference between lecturers and students.